The Use of Autologous Cell Therapy in Diabetic Patients with Chronic Limb-Threatening Ischemia - Sojakova, Dominika; Husakova, Jitka; Fejfarova, Vladimira; Nemcova, Andrea; Jarosikova, Radka; Kopp, Simon; Lovasova, Veronika; Jude, Edward B; Dubsky, Michal (International journal of molecular sciences, 2024)
Autologous cell therapy (ACT) is primarily used in diabetic patients with chronic limb-threatening ischemia (CLTI) who are not candidates for standard revascularization. According to current research, this therapy has been shown in some studies to be effective in improving ischemia parameters, decreasing the major amputation rate, and in foot ulcer healing. This review critically evaluates the efficacy of ACT in patients with no-option CLTI, discusses the use of mononuclear and mesenchymal stem cells, and compares the route of delivery of ACT. In addition to ACT, we also describe the use of new revascularization strategies, e.g., nanodiscs, microbeads, and epigenetics, that could enhance the therapeutic effect. The main aim is to summarize new findings on subcellular and molecular levels with the clinical aspects of ACT.
Keywords: Cell- and Tissue-Based Therapy; chronic limb-threatening ischemia; Humans; buněčná a tkáňová terapie; autologní transplantace; chronická kritická ischemie končetin; Ischemia; transplantace mezenchymálních kmenových buněk; lidé; Mesenchymal Stem Cell Transplantation; peripheral artery disease; diabetes mellitus; Chronic Limb-Threatening Ischemia; Transplantation, Autologous; Diabetes Mellitus; stem cell therapy; ischemie